Preparation method and application of sodium ion layered oxide cathode material nickel iron sodium manganate
By introducing alkali metal/alkaline earth metal elements into Ni/Fe/Mn-based ternary cathode material, a sodium ion layered oxide cathode material was prepared, which solved the problems of irreversible phase change and air sensitivity during the circulation process, and achieved high capacity and stable cycling performance.
Patent Information
- Application Number
- CN202510161725.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing Ni/Fe/Mn-based ternary cathode materials have problems such as irreversible phase change, air sensitivity and capacity attenuation during the cycle, which affects their cycle stability and electrochemical properties.
By mixing the sodium source with alkali metal/alkaline earth metal carbonate, mixing it with Ni/Fe/Mn-based ternary precursor and dispersant, sintering under high temperature conditions, the sodium ion layered oxide positive electrode material sodium niferromanganate NaNi1/3Fe1/3Mn1/3O2 is prepared. This method enhances Na+ diffusion kinetics and stabilizes the layered structure by introducing alkali metal/alkaline earth metal elements.
This method effectively improves the capacity and cycle stability of the cathode material, suppresses phase change during the cycle, improves electrochemical performance, and reduces production costs.
Smart Images

Figure CN119637955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a preparation method and application of sodium nickel iron manganese oxide, a sodium ion layered oxide positive electrode material. Background Art
[0002] Traditional fossil energy sources such as coal, oil, and natural gas are non-renewable and cause serious pollution to the environment. At the same time, with the continuous development of social economy and the growing global population, human demand for energy has also been increasing steadily in the long term. Therefore, some renewable clean energy sources such as wind energy, solar energy, and tidal energy have attracted people's attention, but these energy sources have the characteristics of unstable power generation and intermittent, which makes it difficult to meet the stable demand for energy in today's society. Among them, high-performance secondary batteries that can efficiently and reversibly convert electrical energy and chemical energy have attracted much attention. Among them, lithium-ion batteries (LIBs) have developed rapidly since their commercialization in 1991 due to their high energy density, and are now perfectly integrated into all aspects of human daily life. However, lithium resources, as an important raw material, have low natural abundance, uneven distribution, and high cost. These shortcomings hinder the further development of LIBs. Therefore, we began to look for new secondary batteries that can replace LIBs. Among them, rechargeable sodium-ion batteries (SIBs) are considered to be a promising supplement to the application of lithium-ion batteries in large-scale energy storage systems due to their natural abundance and low cost of sodium resources.
[0003] SIBs are similar to LIBs, both of which are composed of positive and negative electrode materials, electrolytes, separators and current collectors. The positive electrode material is considered to be the key part to improve the power density of SIBs. Transition metal layered oxide positive electrode materials are divided into P2 type and O3 type according to the environment of sodium and the oxygen stacking sequence. Compared with the P2 type positive electrode, the O3 phase positive electrode can accommodate more Na + Enter the interlayer, thus providing a higher reversible capacity. At the same time, when constructing a full battery with a sodium-free negative electrode, the Na + The full content of will not limit the actual capacity. Among the many reported O3-layered structures of ternary transition metal mixtures, the O3– NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (NFM 333) is a promising cathode material with a capacity of >130 mAh / g (0.1C) in the voltage range of 2.0-4.0 V and advantages such as easy synthesis. It is one of the most promising cathode candidate materials, and the use of cost-effective transition metals Fe and Mn further enhances its commercial value. However, Ni / Fe / Mn-based ternary cathode materials will not only undergo irreversible phase transition (O3-P3-P3-O3) during the cycle, but also may cause Na+ / H + Exchange and formation of NaOH and Na2CO3. This air sensitivity requires strict atmosphere control during the storage, transportation and handling of materials, which ultimately increases costs. Problems such as irreversible bulk phase transition, surface structure reconstruction, irreversible oxygen release, and air sensitivity will lead to rapid and reversible capacity decay of positive electrode materials during the cycle. In order to solve these problems, surface coating and element doping methods have been proposed. Although metal oxides coated on the surface of positive electrode materials can successfully prevent electrolyte corrosion and thus enhance electrochemical performance, most of these coating materials are incompatible with Na + Disconnect, reduce Na + Diffusion between layers and charge transfer at the interface. Element doping is one of the simplest and most effective methods to enhance the structural stability of the cathode material and inhibit harmful phase changes, thereby improving the cycle stability. Currently, doped metal ions are mostly introduced into the TM layer to inhibit unfavorable multiphase transitions. For example, non-electrochemically active Al is doped into NFM333 cathode materials to prepare hollow spherical cathode materials; V 5+ Doping into the bulk phase; introducing F into the O3 phase cathode material by sol-gel method - Mg and Ti co-doped O3 phase NaNi 0.5 Mn 0.5 O2, etc. These elements doping can accelerate Na + However, Na site substitution has little effect on improving the structural stability and Na + Diffusion kinetics are also important. This is because the alkali metals + The ionic radius is close, so it is easier to introduce the Na layer during the doping process, which promotes the Na + The diffusion of Ni / Fe and Mn 3+ The Jahn-Teller effect is caused by its unstable layer structure and poor Na + Diffusion channel, NFM333 positive electrode material is prone to phase change during the cycle process, and the cycle performance and rate performance are poor. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a positive electrode material with higher capacity and more stable cycle.
[0005] In view of this, the present invention provides a method for preparing sodium nickel iron manganese oxide, a sodium ion layered oxide positive electrode material, the preparation method comprising the following steps: (1) uniformly mixing a sodium source and an alkali metal / alkaline earth metal carbonate; (2) mixing the material mixed in step (1) with a Ni / Fe / Mn-based ternary precursor and a dispersant to obtain a mixture; (3) Sintering the mixture obtained in step (2) under high temperature conditions to obtain a sodium ion layered oxide positive electrode material, sodium nickel iron manganese oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2; The ratio of the sodium source, the alkali metal / alkaline earth metal carbonate and the precursor is 0.8-1:0-0.5:0.5-1, calculated in terms of the molar ratio of sodium:alkali metal / alkaline earth metal:precursor.
[0006] Preferably, the sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate and sodium oxalate.
[0007] Preferably, the alkali metal / alkaline earth metal carbonate comprises one or more of lithium carbonate, calcium carbonate, potassium carbonate and magnesium carbonate.
[0008] Preferably, the dispersant includes one or more of deionized water, ethanol, acetone, and a polymer dispersant.
[0009] Preferably, the Ni / Fe / Mn-based ternary precursor includes a hydroxide precursor and / or a carbonate precursor.
[0010] Preferably, the mixing in step (2) is performed by ball milling, and the conditions for the ball milling are 200-500 r / min for 2-4 h.
[0011] Preferably, the sintering atmosphere is oxygen and / or air.
[0012] Preferably, the sintering comprises the following steps: heating to 500-700°C at a heating rate of 2-10°C / min, sintering at a constant temperature for 3-10 hours, then heating to 800-950°C, and sintering at a constant temperature for 10-20 hours.
[0013] The present invention also provides application of the method described in the above technical solution in preparing sodium ion batteries.
[0014] The present invention also provides a sodium ion battery, which contains sodium nickel iron manganese oxide, a sodium ion layered oxide positive electrode material prepared by the method described in the above technical solution.
[0015] Beneficial effects of the present invention: 1. The present invention improves upon the existing doping ideas, and utilizes the method of introducing alkali metals into the Na layer to obtain a positive electrode material with higher capacity and more stable cycle. The present invention introduces different alkali metal / alkaline earth metal carbonates and sodium sources and precursor materials for sintering preparation, and the alkali metal / alkaline earth metal elements occupy part of the Na layer or transition metal layer, so that the thickness of the Na layer is increased, thereby enhancing the Na+ diffusion kinetics. As the charging process proceeds, the non-electrochemically active alkali metal / alkaline earth metal elements do not migrate, and play a vital role in supporting the layered structure and maintaining the stability of the crystal structure, thereby achieving improvement in the electrochemical performance of the O3-Ni / Fe / Mn-based ternary positive electrode material by suppressing the phase change during the cycle.
[0016] 2. The raw materials used in the preparation method of the present invention have a wide range of sources, low cost, simple preparation process, little pollution to the environment, and no dust pollution, which is conducive to product scale and commercialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0018] Figure 1 XRD patterns of samples prepared in Example 1 and Comparative Example 1; Figure 2 This is the SEM image of the sample prepared in Example 1; Figure 3 The cycle performance diagram of the samples prepared in Example 1 and Comparative Example 1 at 1C rate; Figure 4 XRD diagrams of samples prepared in Example 2 and Comparative Example 1; Figure 5 This is the SEM image of the sample prepared in Example 2; Figure 6 The cycle performance diagram of the samples prepared in Example 2 and Comparative Example 1 at 1C rate; Figure 7 XRD diagrams of samples prepared in Example 3 and Comparative Example 2; Figure 8 This is the SEM image of the sample prepared in Example 3; Fig. 9 The graph is a cycle performance diagram of the samples prepared in Example 3 and Comparative Example 2 at a 1C rate. DETAILED DESCRIPTION
[0019] The present invention provides a method for preparing sodium nickel iron manganese oxide, a sodium ion layered oxide positive electrode material, the preparation method comprising the following steps: (1) uniformly mixing a sodium source and an alkali metal / alkaline earth metal carbonate; (2) mixing the material mixed in step (1) with a Ni / Fe / Mn-based ternary precursor and a dispersant to obtain a mixture; (3) Sintering the mixture obtained in step (2) under high temperature conditions to obtain a sodium ion layered oxide positive electrode material, sodium nickel iron manganese oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2; The ratio of the sodium source, the alkali metal / alkaline earth metal carbonate and the precursor is 0.8-1:0-0.5:0.5-1, calculated in terms of the molar ratio of sodium:alkali metal / alkaline earth metal:precursor.
[0020] The present invention firstly mixes the sodium source and the alkali metal / alkaline earth metal carbonate uniformly.
[0021] In the present invention, the sodium source preferably includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate and sodium oxalate; the alkali metal / alkaline earth metal carbonate preferably includes one or more of lithium carbonate, calcium carbonate, potassium carbonate and magnesium carbonate. The present invention utilizes alkali metal / alkaline earth metal carbonate doping to obtain a positive electrode material with more stable performance, which can effectively improve the disadvantage of fast material attenuation.
[0022] The present invention mixes the sodium source and the alkali metal / alkaline earth metal carbonate uniformly, and then mixes the mixture with a Ni / Fe / Mn-based ternary precursor and a dispersant to obtain a mixture.
[0023] In the present invention, the dispersant includes one or more of deionized water, ethanol, acetone, and a polymer dispersant; the polymer dispersant is preferably a polycarboxylate dispersant.
[0024] The Ni / Fe / Mn-based ternary precursor of the present invention includes a hydroxide precursor and / or a carbonate precursor. The present invention has no special limitation on the source of the Ni / Fe / Mn-based ternary precursor, and any conventional commercial product may be used.
[0025] The mixing of the present invention is preferably ball milling, and the conditions of the ball milling are preferably 200-500 r / min ball milling for 2-4 hours.
[0026] After obtaining the mixture, the present invention sintered the mixture under high temperature conditions to obtain sodium ion layered oxide positive electrode material sodium nickel iron manganese oxide.
[0027] In the present invention, the sintering atmosphere is preferably oxygen and / or air; the sintering preferably includes the following steps: heating to 500-700°C at a heating rate of 2-10°C / min, sintering at a constant temperature for 3-10 hours, then heating to 800-950°C, and sintering at a constant temperature for 10-20 hours. In a preferred embodiment of the present invention, the sintering preferably includes the following steps: heating to 700°C at a heating rate of 5°C / min, sintering at a constant temperature for 5 hours, cooling down, taking out and grinding, then heating to 950°C, and sintering at a constant temperature for 10 hours.
[0028] The present invention also provides application of the method described in the above technical solution in preparing sodium ion batteries.
[0029] The present invention also provides a sodium ion battery, which contains sodium nickel iron manganese oxide, a sodium ion layered oxide positive electrode material prepared by the method described in the above technical solution.
[0030] In order to further illustrate the present invention, the preparation method and application of a sodium ion layered oxide positive electrode material sodium nickel iron manganese oxide provided by the present invention are described in detail below in combination with the accompanying drawings and examples, but they should not be understood as limiting the scope of protection of the present invention.
[0031] Example 1 (1) Dissolve 0.03 mol calcium carbonate (40 nm) and 0.50 mol sodium carbonate in anhydrous ethanol in a molar ratio and ultrasonically disperse for 30 min. Grind and mix evenly after drying. (2) Add 0.55 mol of NFM hydroxide precursor (4.5 μm, purchased from Henan Kelong) and polymer dispersant (polycarboxylate dispersant), and mix by ball milling at 400-500 r / min for 4 h to obtain solid powder; (3) The solid powder was placed in a muffle furnace under air atmosphere, heated to 700°C at a heating rate of 5°C / min, sintered at a constant temperature for 5 h, cooled, taken out and ground, and then heated to 950°C and sintered at a constant temperature for 10 h to obtain Na 0.96 Ca 0.02 Ni 1 / 3Fe 1 / 3 Mn 1 / 3 O2 positive electrode material. Its performance was tested and the results were as follows Figure 1~Figure 3 shown.
[0032] Example 2 (1) Weigh 0.01 mol potassium carbonate and 0.10 mol sodium carbonate and mix them evenly; (2) adding 0.22 mol of NFM hydroxide precursor (4.5 μm) and mixing to obtain a solid powder; (3) Sintering the solid powder. The sintering steps are the same as step (3) of Example 1. The obtained solid product is Na 0.9 K 0.1 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode material. Its performance diagram is as follows Figure 4~Figure 6 shown.
[0033] Example 3 (1) Weigh 0.01 mol lithium carbonate and 0.28 mol sodium carbonate and mix them evenly; (2) adding 0.55 mol of NFM hydroxide precursor (4.5 μm) and mixing to obtain a solid powder; (3) Sintering the solid powder. The sintering steps are the same as step (3) of Example 1. The obtained solid product is Na 0.9 Li 0.04 (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.987 O2 positive electrode material. Its performance diagram is as follows Figure 7~Figure 9 shown.
[0034] Comparative Example 1 (1) Weigh 0.17 mol of sodium carbonate and 0.33 mol of NFM hydroxide precursor (4.5 μm) and mix them evenly to obtain a solid powder; (2) Sintering the solid powder. The sintering steps are the same as step (3) of Example 1. The obtained product is NaNi 1 / 3Fe 1 / 3 Mn 1 / 3 O2 positive electrode material.
[0035] Comparative Example 2 (1) Weigh 0.17 mol of sodium carbonate and 0.33 mol of NFM hydroxide precursor (4.5 μm) and mix them evenly to obtain a solid powder; (2) Sintering the solid powder. The sintering steps are the same as step (3) of Example 1. The obtained product is NaNi 1 / 3Fe 1 / 3 Mn 1 / 3 O2 positive electrode material. Charge and discharge tests were performed at 2-4.2V.
[0036] It can be found from the accompanying drawings that the three materials of the embodiment and the comparative example were tested and compared by X-ray diffraction analysis, and all belonged to the R-3m space group of the α-NaFeO2 structure, and the diffraction peak corresponded to the O3 phase structure, indicating that the doping of trace alkali metal / alkaline earth metal elements has no destructive effect on the crystal structure of NFM333. The sharp main peaks of the two materials represent the high crystallinity of the materials. In addition, no other obvious heterogeneous phase peaks were observed in the figure. The electrochemical performance diagram also shows that the doping of trace alkali metal / alkaline earth metal elements can effectively improve the discharge performance and cycle performance of the positive electrode material during the cycle process.
[0037] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing sodium ion layered oxide positive electrode material sodium nickel iron manganese oxide, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing a sodium source and an alkali metal / alkaline earth metal carbonate; (2) mixing the material mixed in step (1) with a Ni / Fe / Mn-based ternary precursor and a dispersant to obtain a mixture; (3) Sintering the mixture obtained in step (2) under high temperature conditions to obtain a sodium ion layered oxide positive electrode material, sodium nickel iron manganese oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2; The ratio of the sodium source, the alkali metal / alkaline earth metal carbonate and the precursor is 0.8-1:0-0.5:0.5-1, calculated in terms of the molar ratio of sodium:alkali metal / alkaline earth metal:precursor.
2. The preparation method according to claim 1, characterized in that: The sodium source includes one or more of sodium carbonate, sodium bicarbonate, sodium acetate and sodium oxalate.
3. The preparation method according to claim 1, characterized in that: The alkali metal / alkaline earth metal carbonate includes one or more of lithium carbonate, calcium carbonate, potassium carbonate and magnesium carbonate.
4. The preparation method according to claim 1, characterized in that: The dispersant includes one or more of deionized water, ethanol, acetone, and polymer dispersants.
5. The preparation method according to claim 1, characterized in that: The Ni / Fe / Mn-based ternary precursor includes a hydroxide precursor and / or a carbonate precursor.
6. The preparation method according to claim 1, characterized in that: The mixing in step (2) is ball milling, and the conditions for the ball milling are 200-500 r / min and 2-4 h.
7. The preparation method according to claim 1, characterized in that: The sintering atmosphere is oxygen and / or air.
8. The preparation method according to claim 1, characterized in that: The sintering comprises the following steps: heating to 500-700° C. at a heating rate of 2-10° C. / min, sintering at a constant temperature for 3-10 hours, then heating to 800-950° C., and sintering at a constant temperature for 10-20 hours.
9. Use of the method according to any one of claims 1 to 8 in the preparation of sodium ion batteries.
10. A sodium ion battery, characterized in that: The sodium ion battery contains sodium nickel iron manganese oxide, a sodium ion layered oxide positive electrode material prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Super-high valence metal ion modified sodium ferronickel manganate positive electrode material and preparation method thereof
CN116504950A
Inert metal ion doped nickel iron sodium manganate ternary positive electrode material and preparation method thereof
CN116646514A
Single crystal type layered oxide sodium ion battery positive electrode material and preparation method thereof
CN118908304A
Ion-doped low-nickel layered oxide sodium ion battery positive electrode material and preparation method thereof
CN119297267A
Method for improving air stability of sodium ion layered oxide, material, and use
WO2024178885A1
Cited By
Layered transition metal oxide positive electrode material of sodium-ion battery as well as preparation method and application of layered transition metal oxide positive electrode material
CN120646926A